WOMEN, LABOUR AND HEALTH IN A RECENTLY COLONIZED REGION IN SOUTHERN BRAZIL: A GENDER APPROACH - Pívaro Stadniky, Hilda (2000)
Although Women Studies are sometimes relegated to a marginal and restricted area of knowledge, they have shown their ability to reconstitute social facts and to empower focuses and approaches of the object of history1. Thematics on women makes possible the historicizing of certain concepts and categories such as the relationship of gender, reproduction, family, citizenship, public and private life, expropriation and health, with the aim of transcending and overcoming concepts and values considered proper to the female nature.